2010
DOI: 10.3109/10641950902968593
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Levels Including Oxidized LDL in Women with History of Preeclampsia

Abstract: Preeclampsia (PE), a leading cause of maternal and perinatal morbidity and mortality worldwide, is a hypertensive disorder of unknown aetiology characterized by proteinuria, coagulation abnormalities and different systemic manifestations. Since there are no studies regarding the evaluation of oxidized LDL (oxLDL) in women with a history of PE, we focused on the evaluation of lipid profile and oxLDL plasma concentration several years after pregnancy to see if these women have any modifications in these paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…These discrepancies may stem from the differences in the severity of preeclampsia, and the time elapsed since preeclampsia between the four studies. Some studies have found an increased level of highdensity lipoprotein and triglycerides [81,82], whereas others have reported similar levels of plasma lipids as compared with controls [83,84]. Further research is needed in this area.…”
Section: Lipidsmentioning
confidence: 87%
“…These discrepancies may stem from the differences in the severity of preeclampsia, and the time elapsed since preeclampsia between the four studies. Some studies have found an increased level of highdensity lipoprotein and triglycerides [81,82], whereas others have reported similar levels of plasma lipids as compared with controls [83,84]. Further research is needed in this area.…”
Section: Lipidsmentioning
confidence: 87%
“…Weighted mean values for HDL-C and LDL-C are displayed in Figure 3(c) and ( d ). 35 , 71 , 72 , 74 , 80 , 81 , 84 , 89 , 91 , 95 , 99 103 , 106 111 , 113 , 114 , 117 119 The large standard deviation for mean HDL-C in the 10-year post-partum group is because this category yields only one study. 89 …”
Section: Resultsmentioning
confidence: 99%
“…68,69 When two manuscripts were published on the same cohort, the oldest was excluded. 7072
Figure 1.Flowchart (last search 20 October 2015). HDP: hypertensive disorder during pregnancy
…”
Section: Resultsmentioning
confidence: 99%
“…10 Similarly, Portelinha et al reported an association between obesity anthropometric markers (BMI and WHR) in women with a history of pre eclampsia. 11 Significantly raised levels of VLDL were reported in patients who developed preeclampsia in a study by Kumari et al 12 Though in the present study, the WHR showed a strong positive correlation with the BMI, it is worth noting that mean BMI of the subgroup of women with WHR>0.80 (mean BMI 21.1 Kg/m 2 ; range 18-25Kg/m 2 ; SD±1.5), was in the normal range for Indian population i.e. <23Kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%